Persistence and reactivation of human adenoviruses in the gastrointestinal tract. (April 2016) - Kosulin, K.; Geiger, E.; Vécsei, A.; Huber, W.-D.; Rauch, M.; Brenner, E.; Wrba, F.; Hammer, K.; Innerhofer, A.; Pötschger, U.; Lawitschka, A.; Matthes-Leodolter, S.; et al.
Abstract: Reactivation of persistent human adenoviruses (HAdVs) is associated with high morbidity and mortality in paediatric haematopoietic stem cell transplant (HSCT) recipients. Although invasive HAdV infections mainly arise from the gastrointestinal (GI) tract, the specific sites of HAdV persistence are not well characterised. We prospectively screened biopsies from 143 non-HSCT paediatric patients undergoing GI endoscopy and monitored serial stool specimens from 148 paediatric HSCT recipients for the presence of HAdV by real-time PCR. Persistence of HAdV in the GI tract was identified in 31% of children, with the highest prevalence in the terminal ileum. In situ hybridisation and immunohistochemistry identified HAdV persistence in lymphoid cells of the lamina propria, whereas biopsies from five transplant recipients revealed high numbers of replicating HAdV in intestinal epithelial cells. The prevalence of HAdV species, the frequencies of persistence in the GI tract and reactivations post transplant indicated a correlation of intestinal HAdV shedding pre-transplant with high risk of invasive infection. HAdV persistence in the GI tract is a likely origin of infectious complications in immunocompromised children. Intestinal lymphocytes represent a reservoir for HAdV persistence and reactivation, whereas the intestinal epithelium is the main site of viral proliferation preceding dissemination. The findings have important implications for assessing the risk of life-threatening invasive HAdV infections.